Exploring Travelers’ Attitudes and Willingness to Pay for Sustainable Hotel Practices in Kathmandu - Thapa, Samjhana; Nagarkoti, Rolisha; Gurung, Sabin; Rai, Samikshya; Thapa Magar, Sumita; Rai, Sunandan (International Journal of Atharva, 2025)
Background: Growing environmental concerns are prompting travelers to reconsider the ecological impact of tourism. Hotels, as significant consumers of resources, are adopting eco-friendly practices, though these often necessitate higher operating costs. This creates a critical challenge: determining whether guests are genuinely willing to pay a premium for sustainable accommodations. Objectives: This study aims to bridge the gap between hoteliers' investments in sustainability and their understanding of guest perceptions. It seeks to examine travelers' attitudes, awareness, and willingness to pay (WTP) for eco-certified hotels and the factors influencing their booking decisions. Methods: A quantitative, descriptive research design was employed. A structured questionnaire was distributed to 200 participants in Kathmandu using convenience sampling. Data were collected both online and in-person from guests at various budget to mid-range hotels engaged in sustainable practices. Analysis was performed using frequency distributions and percentages. Findings: The findings reveal a strong positive attitude towards eco-friendly hotels, with 76% of respondents actively seeking them and 72.5% believing they contribute to environmental protection. However, willingness to pay a 5-10% price premium was mixed: only 36.5% definitively agreed, while 47.5% were uncertain. Key motivators for paying more included support for local communities (59.5% agree/strongly agree) and zero-waste policies (58.5% agree/strongly agree). Major barriers identified were a lack of awareness (64% agree/strongly agree) and limited availability (57% agree/strongly agree) of certified options. Most respondents (76%) plan to prioritize sustainable hotels in the future and support mandatory sustainability certifications (71%). Conclusion: There is a significant disconnect between travelers' positive attitudes toward sustainable hotels and their readiness to pay extra. Awareness and availability are greater barriers than cost itself for many. Implication: For hoteliers, success hinges on demonstrating the value of sustainable practices through education, transparency, and promotions. To overcome the awareness barrier, targeted marketing and leveraging peer recommendations are essential. Policymakers and institutions can foster adoption by promoting certifications and considering cost-sharing initiatives to incentivize sustainable choices.